AN INTEGRATED POSYANDU ASSISTANCE (SUPPORT PMT AND EDUCATION ON CHILD NUTRITION) IN MLAJAH VILLAGE - Siti Rochimatul Lailiyah (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2023)
Currently, Indonesia is a country with a high prevalence of stunting compared to other middle-income countries. Toddlers/Baduta (Babies under the age of two) who are stunted will have a level of intelligence that is not optimal, making children more susceptible to disease and in the future can be at risk of decreasing productivity levels. In the end, stunting broadly will hamper economic growth, increase poverty and widen inequality. If this situation is not resolved, it can affect Indonesia's development performance both in terms of economic growth, poverty and inequality(Kemenkes, 2020) . Stunting is still a national issue that still needs serious attention with the prevalence of stunting under five of 30.8% in 2018. This is related to the quality of Indonesia's human resources. The 2021 family data census found data on 21.9 million families at risk of stunting. Still through community empowerment activities in the form of posyandu which are carried out by PKK mothers in almost every village. Posyandu is a form of health effort originating from the community, in which it is implemented from, by and with the community, Posyandu has a very important role and has long been proven to be able to overcome problems related to maternal and child health, nutrition, immunization, infectious diseases and has an effect on reducing maternal and child mortality (Ministry of Health, 2011). One form of early detection efforts is monitoring the growth of children's health at the posyandu in the form of weighing toddlers every month, in this case the mother of the toddler visits every month to monitor the growth and development of the toddler at the posyandu, providing PMT and health education on nutrition for children